2018
DOI: 10.2497/jjspm.65.342
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Reliability and Segregated Manganese Behavior on Multilayered (Li,Na,K)NbO<sub>3</sub> Piezoceramics with Pd Electrodes

Abstract: Multilayered (Li,Na,K)NbO 3 lead-free piezoceramics with Pd inner-electrodes were fabricated by controlling the additive amounts of x mol% MnCO 3 (x = 0.0, 0.5, 1.0, and 2.0) together with other additives. The multilayered samples containing the Mn compound had a markedly increase in electric resistivity from the order of 10 7 to 10 11 Ω•cm at 100°C. Moreover, the normalized electric-field-induced strains for x = 1.0 were over 350 pm/V at 5 kV/mm. The Mn distributions in several multilayered samples were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The driving electric field of 16 kV mm −1 in MLPC-L had markedly high electric fields than other multilayer piezoceramics using alkaline niobate ceramics. [33][34][35][36][37][38][39][40] This is due to the high densification of MLPC-L, as discussed previously.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The driving electric field of 16 kV mm −1 in MLPC-L had markedly high electric fields than other multilayer piezoceramics using alkaline niobate ceramics. [33][34][35][36][37][38][39][40] This is due to the high densification of MLPC-L, as discussed previously.…”
Section: Resultssupporting
confidence: 52%
“…In terms of additive effects, our previous study of Li, Si, and Mn additives in LNKN ceramic concluded that these compounds do not provide a large shift of phase transition and Si and Mn compounds were segregated in the LNKN ceramic body. 38,40) Moreover, the addition of Ba at 0.5 at% did not change the phase transition of the (Na,K)NbO 3 ceramic. 43) Therefore, the changes in the Curie temperature and the monoclinictetragonal phase transition temperature of MLPC-L imply the existence of solid solutions of Ag in the perovskite structure, as also shown by the SEM-EDS results.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The various candidate materials such as (K,Na) NbO 3 -based and (Bi,Na)TiO 3 -based materials and (Sr,Ca) 2 NaNb 5 O 15 , and bismuth layer-structured ferroelectrics have been actively studied not only from the viewpoint of environmental conservation but also for deriving new values from the lead-free materials the advantages of which are deficient in PZT ceramics. [11][12][13][14][15][16][17][18][19][20][21][22][23] That is, PZT ceramics easily experience a large strain and produce a noticeable nonlinearity under practical use condition as the high-power properties, which increase heat generation with decreasing quality factor and deteriorate the piezoelectric performance. Some lead-free piezoelectric materials have high heat resistance and strength and superior high-power properties and so on, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The various candidate materials, such as (K,Na)NbO 3 -based and (Bi,Na)TiO 3 -based materials and (Sr,Ca) 2 NaNb 5 O 15 , and bismuth layer-structured ferroelectrics, have been actively studied not only from the viewpoint of environmental conservation but also for deriving new values from the lead-free materials, the advantages of which are deficient in PZT ceramics. [9][10][11][12][13][14][15][16][17][18][19][20][21] That is, PZT ceramics easily experience a large strain and produce a notable degree of nonlinearity under practical use conditions as the high-power properties, which increase heat generation with decreasing quality factors and deteriorate the performance of PZT ceramics. The lead-free piezoelectric materials have high heat resistance, strength and superior high-power properties and so on, respectively.…”
Section: Introductionmentioning
confidence: 99%